Signaling to stomatal initiation and cell division - Le, Jie; Zou, Junjie; Yang, Kezhen; Wang, Ming (Frontiers in Plant Science, 2014)
Stomata are two-celled valves that control epidermal pores whose opening and spacing optimizes shoot-atmosphere gas exchange. Arabidopsis stomata formation undergoes at least one asymmetric division and a symmetric division. Frequency and placement of asymmetric divisions regulate stomatal production and pattern. Stomatal development is a remarkably accessible model system that has already yielded impressive advances in plant developmental biology, such as the regulation of cell fate, division, differentiation, and patterning. During the past 30 years, many results demonstrate that stomatal development is controlled by many intrinsic genetic and environmental factors. In this mini review we will focus the signaling to stomatal initiation and divisions.